The non-pathogenic protozoon Leishmania tarentolae interferes with the activation of NLRP3 inflammasome in human cells: new perspectives in the control of inflammation - La Rosa, Francesca; Varotto-Boccazzi, Ilaria; Saresella, Marina; Marventano, Ivana; Cattaneo, Giulia Maria; Hernis, Ambra; Piancone, Federica; Otranto, Domenico; Epis, Sara; Bandi, Claudio; Clerici, Mario (Frontiers in Immunology, 2024)
Background Innate immune responses against infectious agents can act as triggers of inflammatory diseases. On the other hand, various pathogens have developed mechanisms for the evasion of the immune response, based on an inhibition of innate immunity and inflammatory responses. Inflammatory diseases could thus be controlled through the administration of pathogens or pathogen-derived molecules, capable of interfering with the mechanisms at the basis of inflammation. In this framework, the NLRP3 inflammasome is an important component in innate antimicrobial responses and a major player in the inflammatory disease. Parasites of the genus Leishmania are master manipulators of innate immune mechanisms, and different species have been shown to inhibit inflammasome formation. However, the exploitation of pathogenic Leishmania species as blockers of NLRP3-based inflammatory diseases poses safety concerns. Methods To circumvent safety issues associated with pathogenic parasites, we focused on Leishmania tarentolae, a species of Leishmania that is not infectious to humans. Because NLRP3 typically develops in macrophages, in response to the detection and engulfment microorganisms, we performed our experiments on a monocyte-macrophage cell line (THP-1), either wild type or knockout for ASC, a key component of NLRP3 formation, with determination of cytokines and other markers of inflammation. Results L. tarentolae was shown to possess the capability of dampening the formation of NLRP3 inflammasome and the consequent expression of pro-inflammatory molecules, with minor differences compared to effects of pathogenic Leishmania species. Conclusion The non-pathogenic L. tarentolae appears a promising pro-biotic microbe with anti-inflammatory properties or a source of immune modulating cellular fractions or molecules, capable of interfering with the formation of the NLRP3 inflammasome.